ADVANCED ACCOUNTANCY VOL - II - JAIN S P; K L NARANG; SIMMI AGARWAL; MONIKA SEHGAL (LUDHIANA KALYANI, 2023)
"Advanced Accountancy, Vol. 2" by S.P. Jain and K.L. Narang is a comprehensive textbook that delves into the intricacies of corporate accounting. Published by Kalyani Publishers, this book is an essential resource for those looking to build a strong foundation in the financial accounting and reporting of companies. In its recent editions, the book is often co-authored by Simmi Agrawal and Monika Sehgal, ensuring the content remains current and relevant.
ACCOUNTING
BBA & MBA
Keywords: ACCOUNTING; MANAGEMENT